2008
DOI: 10.1021/jp808355y
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of V−V Transfer Rates in H2 and Comparison with Experiment

Abstract: Recent observations on VV transfer in H(2) have shown interesting results. For nonresonant processes, comparison of the experimental rate constants with the results of previous semiclassical calculations, quantum oscillators/classical rotors coupled via classical collisions, showed the theoretical rate constants to be too slow by a factor of 3 or more. The semiclassical rate constant of the resonant VV process (v = 1 + v = 0 --> v = 0 + v = 1) was also found to be too slow, by more than an order of magnitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[1] In particular, azole-annulated 1,2,3-triazines possess activity as anti-virals and anti-tubercular agents, inhibitors of protoporphyrinogen oxidase, herbicides, and pesticides, among others. [2][3][4] In view of the important biological activities of purine analogues, our research interests have been focused on the synthesis of pyrazolo [3,4-d][1,2,3]triazin-4-ones and imidazo [4,5-d][1,2,3]triazin-4-ones, establishing a convenient method to access a broad range of these derivatives through the one-pot diazotization of 5-aminoazole-4-carbonitrile precursors. [5,6] We found that the stability and transformations of the diazonium ion intermediate was strongly dependent on the type of azole ring and, to a lesser extent, the nature of the substituent at N-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In particular, azole-annulated 1,2,3-triazines possess activity as anti-virals and anti-tubercular agents, inhibitors of protoporphyrinogen oxidase, herbicides, and pesticides, among others. [2][3][4] In view of the important biological activities of purine analogues, our research interests have been focused on the synthesis of pyrazolo [3,4-d][1,2,3]triazin-4-ones and imidazo [4,5-d][1,2,3]triazin-4-ones, establishing a convenient method to access a broad range of these derivatives through the one-pot diazotization of 5-aminoazole-4-carbonitrile precursors. [5,6] We found that the stability and transformations of the diazonium ion intermediate was strongly dependent on the type of azole ring and, to a lesser extent, the nature of the substituent at N-1.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] We found that the stability and transformations of the diazonium ion intermediate was strongly dependent on the type of azole ring and, to a lesser extent, the nature of the substituent at N-1. [6] Concerning the chemical reactivity of azole-annulated 1,2,3triazinones, it has been found that modifications at the carbonyl group lead to 4-substituted azolo-triazines, [2,4,7] alkylation at N-3 [8] and opening of the triazine ring with elimination of nitrogen afford pyrazole derivatives [9][10][11][12] or pyrazolyl-pyrazolooxazinones by the dimerization of an iminoketene intermedi-pyrazolotriazinones involves the generation of an iminoketene intermediate, which reacts with a second molecule of pyrazolotriazinone. The complete mechanism of product formation involving the iminoketene intermediate, and all other reasonable pathways, have been explored in detail through DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, deficiencies in the theory are corrected, leading to predictions which compare sensibly with experiment [22,24,25]. Two additional notable quantum approaches to SERS based upon density-matrix calculations have recently appeared in the literature [26,27]. The interaction of a Raman-active molecule supporting two electronic states (plus several vibrational substates) with two nearby nanoscale Ag spheres, described through an extended Mie theory, is presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in Ref. [27], enhanced resonance Raman phenomena are studied within a combined eight-state density-matrix approach where the molecular subsystem is represented in a four-state basis involving molecular ground and electronic, vibrational, and electronic and vibrational excited states while the particle subsystem is represented in a two-state basis consisting of ground and excited states. Within this model, it is predicted that the largest resonance Raman enhancements occur when a molecule, which absorbs light far from the particle's resonance maximum, is excited at the resonance maximum of the particle.…”
Section: Introductionmentioning
confidence: 99%